The level of Emotional Balance and its Relationship to Decision Making Among Police Officers in Zakho Independent Administration (Raparin Journal of Humanities (RJH), 2025)
The current study intends to recognize the emotional balance and decision-making ability of police officers in the Zakho Independent Administration according to variables: years of service، marital status، and participation in courses، as well as to identify the nature of the relationship between emotional balance and decision-making ability. The research sample consisted of (79) officers from the directorates of the Zakho Independent Administration. Also، the researcher employed the descriptive approach in the research. In order to achieve the research objective، the researcher adopted two researching tools، where the emotional balance tool consisted of (30) paragraphs، and decision-making (25) paragraphs. The data included in the research were processed statistically using the Statistical Package for Social Sciences (SPSS) and by applying the following tests: T-test for one sample، T-test for two independent samples، and one-way analysis of variance ANOVA to compare the differences between groups، and finally the LSD test and Pearson's correlation coefficient to estimate the stability of the tools. The results showed that the research sample of police officers had an acceptable level of emotional balance and decision-making according to years of service. There was a difference between two categories; category (1-5) (11- and more) in favor of category (1-5) of emotional balance. There was no difference between the averages of the variable years of service in decision-making as well as there was no difference between the averages of the scores of the research sample members in the level of emotional balance and decision-making according to the variable of participation in the courses. In addition، there was no difference between the averages of the variable social status، emotional balance and decision-making. Lastly، it can be analyzed that there is a statistically significant direct correlation between emotional balance and decision-making.